2014
DOI: 10.1007/s10072-014-1897-z
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reserve in stroke and traumatic brain injury patients

Abstract: Cognitive reserve (CR) is defined as the ability to cope with brain damage due to pre-existing cognitive processes or to the development of new compensatory processes. Existing research on CR is mostly based on the study of neurodegenerative disorders, such as Alzheimer's disease. Recently, however, this construct has also been applied to other neurological conditions, including multiple sclerosis, Parkinson's disease, epilepsy, stroke, and traumatic brain injury. The present review provides an overview of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 31 publications
3
39
1
Order By: Relevance
“…We recently reported that the association between BMI and executive dysfunction is moderated by cognitive reserve (Kirton & Dotson, 2015), which is thought to reflect the ability to optimize performance in the face of brain pathology through differential recruitment of brain networks (Steffener & Stern, 2012; Stern, 2002). Specifically, we found that education—a common proxy for cognitive reserve (Springer, McIntosh, Winocur, & Grady, 2005; Valenzuela, 2008)—protected against BMI-related executive dysfunction, consistent with previous studies demonstrating that individuals with high cognitive reserve have preserved cognitive functioning or less cognitive decline related to various diseases (Chillemi et al, 2015; McLaren, Szymkowicz, Kirton, & Dotson, 2015; Nunnari, Bramanti, & Marino, 2014). …”
Section: Introductionsupporting
confidence: 89%
“…We recently reported that the association between BMI and executive dysfunction is moderated by cognitive reserve (Kirton & Dotson, 2015), which is thought to reflect the ability to optimize performance in the face of brain pathology through differential recruitment of brain networks (Steffener & Stern, 2012; Stern, 2002). Specifically, we found that education—a common proxy for cognitive reserve (Springer, McIntosh, Winocur, & Grady, 2005; Valenzuela, 2008)—protected against BMI-related executive dysfunction, consistent with previous studies demonstrating that individuals with high cognitive reserve have preserved cognitive functioning or less cognitive decline related to various diseases (Chillemi et al, 2015; McLaren, Szymkowicz, Kirton, & Dotson, 2015; Nunnari, Bramanti, & Marino, 2014). …”
Section: Introductionsupporting
confidence: 89%
“…27 In stroke patients, high education seems to be a protective factor against cognitive decline, probably because of preexisting cognitive or compensatory processes. 27 Therefore, highly educated patients may be able to recover faster than lesseducated patients, which possibly explains why cognitive impairment rates were already low at 2 months post stroke, and no significant improvement occurred in the following 4 months. The other subgroups in which no significant recovery was seen represent the most severe stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive reserve has been defined as education, occupational achievement (Murray et al, 2011), intelligence quotient (Koenen et al, 2009), leisurely engagement (Scarmeas et al, 2004), and bilingualism (Schweizer et al, 2012). Measures of cognitive reserve have been successful in predicting clinical status in Alzheimer’s disease (Stern, 2006), HIV (Foley et al, 2012; Shapiro et al, 2014; Stern, 1996), multiple sclerosis (Booth et al, 2013; Schwartz et al, 2013), normal aging (Sole-Padulles et al, 2009; Tucker & Stern, 2011), stroke (Nunnari et al, 2014; Willis & Hakim, 2013), and traumatic brain injury (Levi et al, 2013). However, the neurophysiological mechanisms that facilitate effective assimilation of experience and development of neuroprotective intellectual abilities over the lifespan remain unclear.…”
Section: Problems In Traditional Reserve Researchmentioning
confidence: 99%